1992
DOI: 10.1148/radiology.185.1.1523303
|View full text |Cite
|
Sign up to set email alerts
|

Gastric tumors: radiologic-pathologic correlation and accuracy of T staging with dynamic CT.

Abstract: Incremental dynamic computed tomography (CT) was prospectively performed in 89 patients with gastric tumors (78 gastric cancers, five malignant lymphomas, and six submucosal tumors) after the intake of 400 mL of water, and findings were compared with those obtained at pathologic examination. Dynamic CT of healthy control subjects (15 patients without gastric lesions) showed the gastric wall as a two- or three-layered structure (multilayered pattern): a markedly enhanced inner layer; an intermediate layer of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(81 citation statements)
references
References 0 publications
2
75
0
4
Order By: Relevance
“…Furthermore, the limited spatial resolution often misses tiny metastases [1] . Cho JS suggested that dynamic CT be used to improve the diagnostic accuracy in the preoperative staging of gastric cancer [9] .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the limited spatial resolution often misses tiny metastases [1] . Cho JS suggested that dynamic CT be used to improve the diagnostic accuracy in the preoperative staging of gastric cancer [9] .…”
Section: Resultsmentioning
confidence: 99%
“…Cho JS suggested that dynamic CT be used to improve the diagnostic accuracy in the preoperative staging of gastric cancer [9] . As endoscopic US is invasive and its performance requires special skills [1] , it is difficult to perform on patients with advanced gastric cancer. For MRI, however, no special preparation is required.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations